El sapo de caña o "Bufo" (Rhinella marina) en Florida: UW477/WEC432, 11/2020 - Johnson, Steve A.; Wilson, Audrey; Ubeda, Armando J. (EDIS, 2020)
Spanish language version of: [UW432] The Cane or “Bufo” Toad (Rhinella marina) in Florida https://journals.flvc.org/edis/article/view/104560